2013
DOI: 10.1371/journal.pone.0069149
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Dexamethasone in the Mouse Alters Cardiac Growth Patterns and Increases Pulse Pressure in Aged Male Offspring

Abstract: Exposure to synthetic glucocorticoids during development can result in later cardiovascular and renal disease in sheep and rats. Although prenatal glucocorticoid exposure is associated with impaired renal development, less is known about effects on the developing heart. This study aimed to examine the effects of a short-term exposure to dexamethasone (60 hours from embryonic day 12.5) on the developing mouse heart, and cardiovascular function in adult male offspring. Dexamethasone (DEX) exposed fetuses were gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 64 publications
1
41
2
Order By: Relevance
“…However, when cortisol was infused into the coronary artery of foetal sheep, hyperplasia was induced with only a modest increase in intracardiac cortisol (threefold) and without blood pressure changes (Torres et al 1997, Giraud et al 2006, suggesting a pro-proliferative effect of cortisol on cardiomyocytes. A recent study on mice has administered dexamethasone from E12.5 to E15 (before the normal glucocorticoid surge; O'Sullivan et al 2013). Although this caused a transient decrease in foetal weight and a corresponding though non-significant decrease in foetal heart weight at E14.5, this had recovered by E17.5, possibly as a result of increased cardiac expression of insulin-like growth factor 1, and cardiomyocyte number in adulthood was unchanged (O'Sullivan et al 2013), suggesting compensatory myocardial growth once dexamethasone treatment stopped (though glucocorticoidregulated mRNAs remained elevated at E17.5, indicating a lasting effect of glucocorticoid action on foetal cardiomyocytes).…”
Section: Precocious or Excessive Glucocorticoid Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when cortisol was infused into the coronary artery of foetal sheep, hyperplasia was induced with only a modest increase in intracardiac cortisol (threefold) and without blood pressure changes (Torres et al 1997, Giraud et al 2006, suggesting a pro-proliferative effect of cortisol on cardiomyocytes. A recent study on mice has administered dexamethasone from E12.5 to E15 (before the normal glucocorticoid surge; O'Sullivan et al 2013). Although this caused a transient decrease in foetal weight and a corresponding though non-significant decrease in foetal heart weight at E14.5, this had recovered by E17.5, possibly as a result of increased cardiac expression of insulin-like growth factor 1, and cardiomyocyte number in adulthood was unchanged (O'Sullivan et al 2013), suggesting compensatory myocardial growth once dexamethasone treatment stopped (though glucocorticoidregulated mRNAs remained elevated at E17.5, indicating a lasting effect of glucocorticoid action on foetal cardiomyocytes).…”
Section: Precocious or Excessive Glucocorticoid Actionmentioning
confidence: 99%
“…A recent study on mice has administered dexamethasone from E12.5 to E15 (before the normal glucocorticoid surge; O'Sullivan et al 2013). Although this caused a transient decrease in foetal weight and a corresponding though non-significant decrease in foetal heart weight at E14.5, this had recovered by E17.5, possibly as a result of increased cardiac expression of insulin-like growth factor 1, and cardiomyocyte number in adulthood was unchanged (O'Sullivan et al 2013), suggesting compensatory myocardial growth once dexamethasone treatment stopped (though glucocorticoidregulated mRNAs remained elevated at E17.5, indicating a lasting effect of glucocorticoid action on foetal cardiomyocytes). However, the possibility of foetal HPA axis suppression by dexamethasone treatment was not examined in that study, so it is unclear whether the normal increase in glucocorticoid levels at E16.5-E18.5 occurred in the treated mice and it is likely that the late gestation trajectory of heart maturation was altered in response to dexamethasone.…”
Section: Precocious or Excessive Glucocorticoid Actionmentioning
confidence: 99%
“…However, maternal glucocorticoids may not directly cause the hypertension in the offspring [94]. It has been suggested that the inconsistency in the increase in BP after prenatal exposure to glucocorticoids in rodents could indicate that hypertension becomes apparent only under stressed conditions and that the use of tail cuff to measure BP contributed to the irregularity [95]. The absence of glucocorticoid-inducible kinase SGK1 in the mother prevents the ability of prenatal protein restriction to increase the BP in adult male and female offspring.…”
Section: Pathogenesis Of Primary Pediatric Hypertensionmentioning
confidence: 99%
“…In addition to the direct effects of glucocorticoids, they can indirectly modify the vascular response, too. Glucocorticoids inhibit prostanoid synthesis, and this mechanism also prevents prostanoid induced vasodilatation (O'Sullivan et al, 2013). The decreased level of glucocorticoids, in Addison-disease or after the removal of the adrenals, caused chronic low blood pressure in many patients (Fonyó, 2011).…”
Section: Introductionmentioning
confidence: 99%